Validating 'fit for duty' tests for Australian volunteer fire fighters suppressing bushfires. - Lord, C.; Netto, Kevin; Petersen, A.; Nichols, D.; Drain, J.; Phillips, M.; Aisbett, B. (Elsevier, 2012)
Introduction: This study compared fire fighter’s work-rates and performance between the Pack Hike Test (PHT), Field Walk Test (FWT) and critical bushfire suppression tasks. Methods: Nineteen volunteer fire fighters undertook the PHT, whilst a further 11 also performed the FWT. All 30 fire fighters completed four critical tasks. Physical, physiological and subjective ratings were measured during tasks and tests. Results: Peak and mean heart rate during the Hose Drag was lower than during the FWT. Mean velocities for the PHT and FWT were higher than in all tasks except Hose Drag. Finishing times in the PHT and FWT were strongly correlated with finishing times for three and four of the critical tasks. Conclusions: The PHT and FWT may be valid fit for duty tests for Australian rural fire fighters though the clear differences between the tests and some tasks may prompt fire agencies to consider other tests that more accurately simulate bushfire suppression work.